2016
DOI: 10.1536/ihj.15-459
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Oral Medications for Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a disease that imposes a significant burden on patients. Although multiple treatment options for PAH are available, head-to-head comparisons are difficult to conduct. Network meta-analysis (NMA) can be a useful alternative for direct comparison to estimate the relative effectiveness of multiple treatments. The objective of the present study was to conduct a systematic review and NMA to evaluate the relative effectiveness among oral PAH medications.Data collection was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 27 publications
2
30
0
1
Order By: Relevance
“…33,34) However, the RV is the major determinant of functional state and prognosis in PAH. 35) Thus, PPARγ's advantage lies in offering the possibility of therapies that treat the RV and pulmonary artery as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…33,34) However, the RV is the major determinant of functional state and prognosis in PAH. 35) Thus, PPARγ's advantage lies in offering the possibility of therapies that treat the RV and pulmonary artery as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…They are currently being used in the Measurement of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) analysis was performed in C2C12 myotubes after 2, 6, or 24 h (T0-T24) of tadalafil (1 μM) treatments. Data presented are the mean ± SD of three experiments *p < 0.05 vs CTRL; #p < 0.01 vs CTRL; §p < 0.001 vs CTRL a U/mg protein treatment of pulmonary hypertension (Igarashi et al 2016) and Raynaud's phenomenon (Kamata and Minota 2014). Furthermore, some studies have also reported the protective role of tadalafil in reducing oxidative stress in diabetic animal models (Koka et al 2013;Koka et al 2014;Chen et al 2012;Mostafa et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil inhibits cGMP‐specific PDE5, an enzyme that promotes degradation of cGMP. Inhibition of PDE5 results in smooth muscle relaxation, which alleviates erectile dysfunction and pulmonary arterial hypertension (Balhara et al, ; Igarashi et al ., ). Sildenafil therapy increased HDL‐C and decreased P‐selectin and LDL‐C levels through mechanisms which are not yet understood (Mandosi et al ., ).…”
Section: Pharmaceutical Approachesmentioning
confidence: 99%